2004
DOI: 10.1117/1.1787529
|View full text |Cite
|
Sign up to set email alerts
|

Thermal lensing effects for diode-end-pumped <inline-formula><math display="inline" overflow="scroll"><msub><mi>Nd:YVO</mi><mrow><mn>4</mn></mrow></msub></math></inline-formula> and Nd:YAG lasers

Abstract: The thermal effects of diode-end-pumped Nd:YVO 4 and Nd:YAG lasers are analyzed by a 2-D analytical model and a 3-D numerical model, respectively. The characteristics of the Nd:YVO 4 and Nd:YAG rods are comparatively discussed, including temperature distributions and thermal lensing effects. The model quantitatively separates the end effect from the index parts. Under the same pump configuration, we find that the temperature increase in the Nd:YVO 4 laser was 2 times larger than those in the Nd:YAG laser, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The predicted orientation of the principal meridional planes for a-cut tetragonal crystal agrees with the experimental observations, e.g. for a-cut YVO 4 and GdVO 4 [33][34][35].…”
Section: Refractive Indexsupporting
confidence: 85%
“…The predicted orientation of the principal meridional planes for a-cut tetragonal crystal agrees with the experimental observations, e.g. for a-cut YVO 4 and GdVO 4 [33][34][35].…”
Section: Refractive Indexsupporting
confidence: 85%
“…However, Nd:YVO 4 has low mechanical fracture, thus the pump intensity must be kept under a threshold. It has been shown that the pump power fracture limit of Nd:YVO 4 is inversely proportional to the doping concentration [21]. Therefore, a Nd:YVO 4 crystal with low doped concentration was used to reduce and the length of the doped crystal was decided for high pump absorption efficiency [22,23] Figure 6 (online color at www.lphys.org) Experimental setup of the second solid-state amplifier stage in hybrid amplifier system crystal was used in amplifier system.…”
Section: Dual-end Pumped Composite Nd:yvo 4 Amplifier Systemmentioning
confidence: 99%